2018
DOI: 10.1016/j.lithos.2018.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Apatite: a U-Pb thermochronometer or geochronometer?

Abstract: Apatite is an accessory mineral that is frequently found in both igneous and clastic sedimentary rocks. It is conventionally considered to be characterized by a closure temperature range between 375 and 600°C and hence has been employed to address mid-temperature thermochronology questions relevant to the reconstruction of thermal events in the middle to lower crust. However, questions remain as to whether apatite faithfully records thermally-activated volume diffusion profiles, or rather is influenced by recr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
55
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 128 publications
(58 citation statements)
references
References 60 publications
3
55
0
Order By: Relevance
“…This sample also plots within the same Hf evolution trend as samples 318 and 704, again implying the granite predominately resulted from reworking of the existing tonalitic crust. The zircon crystallization in sample 215 was coeval with the growth of metamorphic apatite in leucosomes within the TTGs (Kirkland et al 2018b). Hf isotope data from the similarly aged 2.55 Ga Qôrqut granite, within the Nuuk region, has a slightly more evolved Hf isotopic signature (Hiess et al 2011;Naeraa et al 2014), interpreted as reflecting melting of an older crustal source than that found outcropping within the Akia Terrane.…”
Section: Later Magmatic and Metamorphic Eventsmentioning
confidence: 91%
“…This sample also plots within the same Hf evolution trend as samples 318 and 704, again implying the granite predominately resulted from reworking of the existing tonalitic crust. The zircon crystallization in sample 215 was coeval with the growth of metamorphic apatite in leucosomes within the TTGs (Kirkland et al 2018b). Hf isotope data from the similarly aged 2.55 Ga Qôrqut granite, within the Nuuk region, has a slightly more evolved Hf isotopic signature (Hiess et al 2011;Naeraa et al 2014), interpreted as reflecting melting of an older crustal source than that found outcropping within the Akia Terrane.…”
Section: Later Magmatic and Metamorphic Eventsmentioning
confidence: 91%
“…Kirkland et al [33] used U-Pb isotope dating of apatite, which has a closure temperature of 375 to 600 • C [34,35], to provide constraints on the lower temperature evolution of the Akia Terrane. That study found evidence for thermal events ranging in age from ca.…”
Section: Pressure-temperature-time Constrains Of Talc Fomationmentioning
confidence: 99%
“…In a very recent paper, Kirkland et al (2018) analyzed compositional and Pb isotopic profiles in apatite. They concluded that "To apply Pb diffusion profiles to determine cooling histories, one must not assume but demonstrate that thermally activated volume diffusion is justifiable because our results show that apatite generally may not record simple thermally activated Pb diffusion profiles but rather profiles modified in part or whole by recrystallization or new growth" (Kirkland et al, 2018, p. 155).…”
Section: Example 1 Monazite Thermochronometry: the Relevance Of Diffmentioning
confidence: 99%